A Design of "SWAFT" Technology for Separation of Fe, Pb, and Cu Metal Waste in Deli River Water Medan (Based on Coagulation-Adsorption Using Activated Carbon from Rice Husks and Aloe Vera Coagulant) - Sinuhaji, Tubagus Rayyan Fitra; Purba, Darly Guntur Darris; Sirait, Hormat Gunawan; Ginting, Setia Rifai Matuanta; Nainggolan, Robby Samuel Meligust; Siahaan, Bungaran Immanuel (Hayyan Journal, 2024)
The increase in population has influenced the rising demand for water, and one way to meet this demand is by utilizing river water. Deli River is one of the rivers that flows through the city of Medan. The development of industries and settlements along the Deli River has affected its water quality due to heavy metal waste, specifically Fe, Pb, and Cu. This is evident from the deterioration of water quality characterized by changes in color and odor. One solution to address this issue is by using rice husk activated carbon as an adsorbent and aloe vera as a biocoagulant. Rice husk contains cellulose which can be converted into carbon and has a carbon content of 48.9%, while aloe vera contains mucilage which is an active coagulant used for water clarification. The principle used in this product is coagulation, which involves mixing chemicals, such as coagulants, with Deli River water followed by the adsorption process, where metal particles accumulate on the surface of the adsorbent. The results obtained showed a decrease in the parameters of Fe, Pb, and Cu metal content successively by 0.0092 mg/liter; 0.0081 mg/liter, and 0.0072 mg/liter. Thus, the filtered water meets the clean water quality standards set by Government Regulation No. 82 of 2001. Based on the existing problems and potentials, this product becomes a smart solution to assist the community, especially those in riverside areas, in water treatment and also addresses the challenges in preparing human resources that are actualized in facing the era 5.0 revolution.